Recent Advances in Directed Assembly of Nanowires or Nanotubes - Liu, Mei; Wu, Zhizheng; Lau, Woon Ming; Yang, Jun (Nano-Micro Letters, 2012)
Nanowires and nanotubes of diverse material compositions, properties and/or functions have been produced or fabricated through various bottom-up or top-down approaches. These nanowires or nanotubes have also been utilized as potential building blocks for functional nanodevices. The key for the integration of those nanowire or nanotube based devices is to assemble these one dimensional nanomaterials to specific locations using techniques that are highly controllable and scalable. Ideally such techniques should enable assembly of highly uniform nanowire/nanotube arrays with precise control of density, location, dimension or even material type of nanowire/nanotube. Numerous assembly techniques are being developed that can quickly align and assemble large quantities of one type or multiple types of nanowires through parallel processes, including flow-assisted alignment, Langmuir-Blodgett assembly, bubble-blown technique, electric/magnetic- field directed assembly, contact/roll printing, knocking-down, etc.. With these assembling techniques, applications of nanowire/nanotube based devices such as flexible electronics and sensors have been demonstrated. This paper delivers an overall review of directed nanowire assembling approaches and analyzes advantages and limitations of each method. The future research directions have also been discussed.